Hubungan Antara Sikap Kerja membungkuk dengan Perubahan kurva Vertebra Pada Kuli Bangunan - Nurhadiono, Hanif Miftahudin, Wahyuni, S.Fis., M.Kes, Dwi Kurniawati, Sst.Ft., M.Kes (2016)
Background: Porter building do his job had risk fatigue, muscle strain, pain and bone twisted. It can be influenced by his attitude of working was like mixing cement, setting of bricks, or painting of wall. The results of pre study was knowing the porter building had suffered kyphosis. The objective of Research: It is expected from this research can increase knowledge and repertoire specifically for field workers in order to better understand the working position. The objective: To know correlation between bend working position with change curve vertebrae of porter building The method of Research: Kind of study was quantitative and use crossectional approach. Samples are 36 porter building who changed a curve vertebrae in Pabelan Surakarta. Measurement curve vertebrae used flexicurve. Result of the Research: Analysis data used chi square test. The result showed respondents position bend ≥200 many change abnormal curve vertebrae while bend position <200 change curve vertebrae normal. Result of chi square test obtained p = 0,008 ( p < 0,05 ) with OR = 6.875 Conclusion: There was correlation between bend working position with change curve vertebrae of porter building. Respondents with position bend ≥200 had 6,875 time higher risk change abnormal curve vertebrae than bend position <200